Assessment of cardiovascular risk in an Italian psychiatric outpatient sample: A chart review of patients treated with second‐generation antipsychotics. (2nd December 2017) - Severi, Elena; Ferrara, Maria; Tedeschini, Enrico; Vacca, Francesca; Mungai, Francesco; Amendolara, Rocco; Baccari, Flavia; Starace, Fabrizio
Abstract: Despite the call by the scientific community for a systematic monitoring of physical health in people with psychiatric illnesses, national and international audits have reported poor quality of cardiovascular risk assessments and management in this vulnerable population. Available evidence indicates that in people affected by mental illness, life expectancy is reduced by 10–20 years, mainly due to cardiovascular accidents and metabolic syndrome (MetS)‐related diseases. The primary aim of the present study was to evaluate the accuracy of cardiovascular risk monitoring in an outpatient sample of patients taking second‐generation antipsychotics. The sample consisted of 200 patients consecutively recruited from two community mental health centres. A clinical chart review was performed on the following laboratory tests: total cholesterol, high‐ and low‐density lipoprotein, serum triglycerides, fasting blood glucose, γ‐glutamyl transpeptidase. Blood pressure and waist circumference were measured. A complete cardiovascular risk assessment was available only in 60 patients out of 200 (33.3%). The only variable associated with laboratory tests for MetS was receiving three or more psychotropic medications, which increased fourfold the probability of metabolic screening. In the subsample of patients with full screening, the prevalence of MetS was 33.3%. Our findings suggest that mental health professionals working in community mental health services should incorporate a more systematic assessment of physical health in their practice, and intervene proactively to reduce the significant cardiovascular burden carried by people with several mental illness.